2016
DOI: 10.1111/trf.13732
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between transfusion volume and outcomes in children undergoing noncardiac surgery

Abstract: RBC transfusion is associated with an increased incidence of 30-day mortality and postoperative infections in children undergoing noncardiac surgery, and there is a correlation between the volume of red blood cells transfused and the incidences of adverse outcomes. Potential associations related to the reason to transfuse, the cause of the bleeding, or the actual blood products themselves need to be studied in further prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
(32 reference statements)
2
40
0
Order By: Relevance
“…Minhas et al performed an analysis of the ACS NSQIP pediatric database including 1,691 patients with idiopathic scoliosis and observed that transfusion was only associated with an increased incidence of complication when transfusion volumes > 20 mL/kg were given . However, it is important to keep in mind that the indication for transfusion also significantly influences outcome and that transfusion of large volumes of blood products are usually required in the presence of massive bleeding, while small volumes are used to increase the hemoglobin in the context of anemia . If RBC transfusion can be used to treat anemia, this option should never be considered as the first line since alternatives exist.…”
Section: Discussionmentioning
confidence: 99%
“…Minhas et al performed an analysis of the ACS NSQIP pediatric database including 1,691 patients with idiopathic scoliosis and observed that transfusion was only associated with an increased incidence of complication when transfusion volumes > 20 mL/kg were given . However, it is important to keep in mind that the indication for transfusion also significantly influences outcome and that transfusion of large volumes of blood products are usually required in the presence of massive bleeding, while small volumes are used to increase the hemoglobin in the context of anemia . If RBC transfusion can be used to treat anemia, this option should never be considered as the first line since alternatives exist.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that longer storage of RBCs was associated with increased risks of infection, renal dysfunction, respiratory failure, multiple organ dysfunction syndrome, deep vein thrombosis, and mortality. In addition, adverse clinical outcomes were more common especially in critically ill patients [11-13]. A study by Cholette et al found that transfusion of washed RBCs and platelets during cardiac surgery reduced postoperative inflammation and number of transfusions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion‐related acute lung injury, transfusion‐related acute circulatory overload, and hemolytic transfusion reactions are the main culprits with mortality rates as high as 15%‐30%. Allogeneic red blood cell transfusion is associated with an increased incidence of 30‐day mortality and complications in children . In order to decrease the risks associated with transfusion of blood products, a concerted effort must be made by all hospitals and health care workers to avoid unnecessary and inappropriate transfusions as well as over‐transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic red blood cell transfusion is associated with an increased incidence of 30-day mortality and complications in children. 15,30 In order to decrease the risks associated with transfusion of blood products, a concerted effort must be made by all hospitals and health care workers to avoid unnecessary and inappropriate transfusions as well as over-transfusion. Management of critical pediatric bleeding using massive hemorrhage guidelines complements Massive Transfusion Protocols (MTP) 23 Neonates, infants, and children are physiologically distinct from adults.…”
mentioning
confidence: 99%